Neurophysiological Changes in Patients with Discirculatory Encephalopathy Associated with Ischemic Optic Neuropathy - T. N. Iureva; A. A. Zaika; V. V. Shprakh; S. I. Zhukova (Acta Biomedica Scientifica, 2020)
Background. The most common chronic cerebrovascular pathology is dyscirculatory encephalopathy, in which a decrease in blood supply due to damage to brachiocephalic vessels leads to damage to brain substances and analyzers, including visual, with the possible development of severe damage in the form of ischemic optic neuropathy. Many studies have been devoted to the relationship between atherosclerotic damage to the neck vessels and ischemic damage to the visual organ, but little attention has been paid to the study of the functional activity of the altered visual analyzer in patients with dyscirculatory encephalopathy, and the results are scattered. Aim. To conduct a comparative analysis of changes in neurophysiological parameters of the brain and visual analyzer in patients with dyscirculatory encephalopathy and patients with a combination of dyscirculatory encephalopathy and ischemic optic neuropathy. Materials and methods. 34 patients with the 2nd stage of dyscirculatory encephalopathy were examined and divided into two groups based on the presence/absence of ischemic optic neuropathy of various prescription periods. All patients underwent ultrasound scanning of neck vessels, visual fields determination, electroretinography, visual evoked potentials, and electroencephalogram. Results. The results revealed changes in a number of indicators in the group of patients with a combination of two diseases: more pronounced atherosclerotic lesion of brachiocephalic vessels, a decrease in the amplitude and the alpharhythm prevalence index, a decrease in oscillatory potentials, a change in latency and amplitudes the visual analyzer according, lengthening of time indicators with a simultaneous decrease in amplitudes and depression of retinal sensitivity. Conclusion. Patients with dyscirculatory encephalopathy complicated by ischemic optic neuropathy have a combined lesion of the brain and visual analyzer, which determines the severity of the detected changes and requires a comprehensive multidisciplinary approach to the treatment of these patients.